Surveillance Following Hepatitis B Surface Antigen Loss: An Issue Requiring Attention - Shuai-Wen Huang; Hong Long; Jia-Quan Huang (Pathogens)
Due to the lack of agents that directly target covalently closed circular DNA and integrated HBV DNA in hepatocytes, achieving a complete cure for chronic hepatitis B (CHB) remains challenging. The latest guidelines recommend (hepatitis B surface antigen) HBsAg loss as the ideal treatment target for improving liver function, histopathology, and long-term prognosis. However, even after HBsAg loss, hepatitis B virus can persist, with a risk of recurrence, reactivation, cirrhosis, and hepatocellular carcinoma. Therefore, follow-up and surveillance are still necessary. With increasing treatment options available for achieving HBsAg loss in patients with CHB, developing effective surveillance strategies has become crucial. Recent studies on outcomes following HBsAg loss provide new insights for refining current surveillance strategies, though further improvement is needed through long-term observation and follow-up.